Perencanaan Kebutuhan Energi Listrik PLTS Hybrid-Off Grid pada Kolam Budidaya Ikan Nila menggunakan Recirculating Aquaculture System (RAS) - Subairi, Subairi; Effendy, Machmud; Sari, Resi Dwi Jayanti Kartika; Arifuddin, Rahman; Ridlo, Muhammad Ali (FORTEI Regional VII Jawa Timur, 2025)
This study aims to design and analyze a Hybrid Off-Grid Solar Power Plant (PLTS) system to support the operation of Nile tilapia farming based on the Recirculating Aquaculture System (RAS) in Parangargo Village, Wagir District, Malang Regency. The location was chosen due to its high solar energy potential, with an average solar irradiation intensity of 4.5–5.2 kWh/m² per day. The research methodology includes identifying RAS electrical load requirements, calculating solar panel capacity, designing an energy storage system using VRLA batteries, and conducting economic analysis. The system is designed to meet a daily energy demand of 4,200 Wh with a solar panel capacity of 1,250 Wp and a battery capacity of 24V 400Ah. The hybrid off-grid configuration allows the PLTS to serve as the primary power source with the grid (PLN) as backup. The analysis results indicate that the system can provide a reliable and environmentally friendly power supply, with operational cost savings of approximately IDR 2.21 million per year and a payback period of around 11.7 years. The implementation of this system has the potential to reduce dependence on the grid, lower production costs, and enhance the operational efficiency of tilapia farming